Private Houses and Graves in the Diyala Region - Delougaz, Pinhas Pierre (1967)
I. Khafajah, by P. Delougaz; II. Tell Asmar, by H. D. Hill and S. Lloyd with remarks by P. Delougaz; III. Tell Agrab, by S. Lloyd; IV. Concluding Remarks, by P. Delougaz; 180s.